Hiromeri: A Specialty Ham of Cyprus-Historical Evidence, Culinary and Cultural Perspectives - Patapiou, Nasa; Lazarou, Chrystalleni (My University, 2013)
Hiromeri is a specialty ham of Cyprus, made of smoked pork leg that is matured in wine. Until now there has been no systematic effort to present historical evidence that will support the Cypriot authenticity of this product. In this article, the historical evidence from sixteenth to twentieth centuries, referring to the production and trade of hiromeri in Cyprus, is presented. The evidence is drawn from archival testimony, travelers' descriptions, old history books, and essays on agricultural production. Moreover, a description of the hiromeri production process as well as past and current culinary uses and customs associated with its production and consumption are presented.
Keywords: Cyprus ham; Deli meat; Hiromeri; Pork slaughtering